Evolution of New Energy Minerals Trade Pattern and Analysis of China’s Status Evolution - Chen, Wei (Transactions on Economics, Business and Management Research, 2024)
Copper, cobalt, nickel as the key raw materials for the new energy automobile industry, the supply and demand of resources and international trade are largely affected by the world economy and political pattern, and the risks and vulnerabilities of the resource industry chain are highlighted. Using the method of complex network to analyze the trade network of three kinds of mineral resources from the perspective of industrial chain, the following conclusions are drawn: (1) the global trade network of three kinds of new energy minerals in the whole industrial chain all presents the characteristics of complexity and connection enhancement, and has the characteristics of the network of the small world; (2) China has become an important hub in the global trade network of copper, cobalt, and nickel, and has a stronger ability to control the trade of other countries.